The narcissistic features and eating disorders in male bodybuilders - Pawłowska, Beata; Stankiewicz, Zofia (Current Problems of Psychiatry, 2011)
The purpose of the study was to investigate the differences in personality traits and symptoms of eating disorders among men regularly practicing and non-practicing in the gym. Examined group: There were examined 30 men, who exercise regularly at the gym (clinical group) and 30 men who do not exercise at the gym (control group). The average age of the respondents in both groups was 26 years. City dwellers were 87% of male bodybuilders and 100% of people not exercising at the gym. In the clinical group: 60% of men had secondary education and 40% - higher. In the control group 17% of respondents had secondary education and 83% - higher. Coming from full family was reported by 73% of male exercisers, and 90% of people not exercising at the gym. Alcohol abuse was reported by 40% of bodybuilders and 23% of non-exercisers. Methods: The study used The Survey by Zofia Stankiewicz, the Eating Disorder Inventory (EDI) by D.M. Garner, M.P. Olmsted and J. Polivy and the Narcissism Inventory (N) by F. Deneke, B. Hilgenstock and R. Müller, in Polish study by Januszewski. Results: Men who exercise regularly at the gym scored significantly lower scores in comparison with non-exercising men in the range of EDI scales: Body dissatisfaction and Ineffectiveness, and significantly higher scores in Perfectionism scale of EDI Inventory and in all scales of factors: “Classic Narcissistic Self "and "Ideal Self” of the Narcissism Inventory. Conclusions: 1. Male bodybuilders feel strong pressure to succeed, gain exceptional achievements in their lives. 2. Male bodybuilders are characterized, in comparison with nonathletes, by significantly more severe greatness, the need to exalt and exaggerate themselves, a sense of special uniqueness concerning physical attractiveness and the need for attracting attention of others. 3. Men who practice regularly at the gym, more often than non-exercisers, treat other people instrumentally, manipulate them to meet their own needs and consider others as superficial, threatening, devoid of ideals, irresponsible, unreliable and disappointing. 4. In a situation of stress and problems, men who practice regularly at the gym, more often than those not exercising, use the defence mechanism of denial and strategies focused on emotions. 5. Male bodybuilders are characterized by severe narcissism and perfectionism. Intense exercises can be a way of drawing attention to themselves, building a sense of their own uniqueness, originality and physical attractiveness, and a form of escape from stress and problems.6. Intensive exercising at the gym and excessive concentration on own figure in men is not connected with disturbed eating behaviours, as it is among women, but with severe perfectionism and narcissistic personality features.